Groundwater Occurrence from Hydrogeomorphological Study of Hard Rock Terrain of Part of Southwestern Nigeria - Akinfemiwa Akanbi Olanrewaju (Materials and Geoenvironment, 2018)
Studies of structural and hydrogeomorphological units (HGU) that are indicators of groundwater occurrence were carried out across an area extent of more than 700 km2 within the hard rock terrain of southwestern Nigeria. These studies integrated geological remote sensing techniques (RST) and geographical information system (GIS) methods to generate thematic maps that included elevation, drainage, lineaments and vegetation index for characterising the attributes of groundwater occurrence across the area. The results revealed that the lineament system is mainly rectilinear with major trends of NNW-SSE and NE-SW on the gneiss, NW-SE and NE-SW on porphyritic granite and NNE-SSW, NW-SE and E-W on migmatite. The discharge zones in the area are the lowland terrains underlain by gneiss and amphibolite. Similarly, variably directional discontinuities that are related to rock contacts are equally laden with groundwater. Conversely, the recharge areas are the high-lying terrains characterised by higher fracture density and underlain by porphyritic granite and migmatite. Additionally, there are evidences of groundwater seepage along the major river channels. Therefore, besides the rock structures, landform is another crucial factor that guides groundwater distribution in the study area.